Pelatihan Penyusunan Business Plan bagi Pelaku Usaha UMKM di Gowa Sulawesi Selatan - Dandan Irawan (E-Coops-Day, 2023)
The success of the business activity is generally always preceded by careful planning. The planning function is part of the management function, constitutes a collection of decisions, and in the business world, is simply interpreted as estimates of the potential and prospects of a business in the future so that problems related to policies and use of resources are resolved. something very important. There are several advantages if business activities begin with business planning (business plan) is good, including (1) Bringing up regular and systematic activities, because planning provides guidelines for the implementation of an activity, (2) Can estimate the potential and prospects that are tangible to intangible, (3) Providing an appropriate and systematic method of dealing with specific constraints, (4) Providing the best opportunity from various alternatives and compiling a combination of available resources, (5) Being the basis for conducting monitoring and evaluation, (6) Providing opportunities in setting priorities and (7) Guiding the use of resource allocations more efficiently and effectively